2010
DOI: 10.1188/10.cjon.567-577
|View full text |Cite
|
Sign up to set email alerts
|

The Caregiving Journey for Family Members of Relatives With Cancer

Abstract: Family caregivers need adequate support from healthcare professionals to complete the demands associated with caregiving with minimal impact on their own health and well-being. An optimal balance of provision of care between family and support services has not been achieved; therefore, this literature review investigates how family caregivers endure and cope with the challenges of caring for an adult relative with cancer. This review considered the characteristics of caregivers and their functioning, the exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 72 publications
(257 reference statements)
5
50
0
Order By: Relevance
“…Other caregivers supported patients by being physically present all the time. This is similar to the findings by Northfield and Nebauer's [45] study of caregivers journey which noted the caregivers desire to be present as proof that they fulfilled their role. In addition, caregivers in this study tried to take patients out as much as possible even when the patients were bedridden.…”
Section: Discussionsupporting
confidence: 79%
“…Other caregivers supported patients by being physically present all the time. This is similar to the findings by Northfield and Nebauer's [45] study of caregivers journey which noted the caregivers desire to be present as proof that they fulfilled their role. In addition, caregivers in this study tried to take patients out as much as possible even when the patients were bedridden.…”
Section: Discussionsupporting
confidence: 79%
“…Quantitative studies have found that the failure to disclose feelings and concerns is associated with low emotional well-being in patients (Reid-Arndt et al, 2009); furthermore, good family communication and higher levels of perceived family support are associated with lower psychological distress in both male and female patients (Hasson'Ohayon et al, 2010;Northfield and Nebauer 2010).On the other hand, others have doubted the assumption that disclosure is good for cancer patients; for example, one study reported that patients often did not like to talk about their impressions with nurses, and instead, they decided to only talk about 'normal life', 'their hobbies' and 'families '(McLeod et al, 2010). Gray (2000) argued that there is no reason to suspect that it is psychologically or socially more adaptive to disclose to family, friends, and acquaintances than to not disclose (Gray et al, 2000).…”
Section: Self-disclosure Of Breast Cancer Diagnosis By Iranian Womenmentioning
confidence: 99%
“…This particular finding supports the indirect relationship between caregiver burden and mental health outcomes through coping style, as posited in the Revised Sociocultural Stress Model . Although there has been limited literature evaluating the coping strategies utilized by cancer caregivers (Northfield & Nebauer, 2010), the positive relationship between caregiver burden and repetitive thinking is consistent with the few articles exploring caregiver burden and maladaptive coping strategies in cancer caregivers (Papastavrou, Charalambous, & Tsangari, 2009;Papastavrou, Charalambous, & Tsangari, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…Second, because repetitive thinking significantly predicts depressive symptoms in cancer caregivers, it may be an important maladaptive coping strategy to examine in continued research, particularly within the context of interventions to support cancer caregivers. Given the limited literature examining coping in cancer caregivers (Northfield et al, 2010), it may be especially helpful to continue to explore how coping strategies may mediate the experience of distress and burden with mental and physical health outcomes. Third, this study explored two particular sections or mediations of the Revised Sociocultural Stress Model , offering support for the role that coping may play in the relationship between burden and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation